Food, gentrification, and the changing city - Sbicca, Joshua, author; FUHEM Ecosocial, publisher (Colorado State University. Libraries, 2018)
Food offers a visceral entry point into the politics and processes of gentrification. Traditional explanations of gentrification - when a neighborhood experiences disinvestment and economic decline followed by "revitalization" and "redevelopment" - hinge on either political economy or cultural drivers. This article discusses the relationship between these two drivers to show how food gentrification is multifaceted and changes neighborhood class and ethnoracial demographics, foodscapes and foodways, and housing. First, poor communities in cities around the world can experience the deleterious effects of food driving gentrification, like when developers use urban agriculture to attract new residents and increase property values. Second, food itself is being gentrified, which for communities marginalized by their race or ethnicity means both the dispossession of culturally important foods that are made "cool" and become unaffordable and the upscaling of food retail that displaces former bars, cafes, restaurants, grocery stores, and gardens. The article concludes with a brief discussion of some social movement strategies and policy approaches that might prevent the harmful effects of food gentrification.
Keywords: food gentrification; green gentrification; political economy; culture; place